Uniform Crime Reporting Program Data (United States): Supplementary Homicide Reports, 1999 ([Verlag nicht ermittelbar], 2001)
Since 1930, the Federal Bureau of Investigation has compiled the Uniform Crime Reports (UCR) to serve as a periodic nationwide assessment of reported crimes not available elsewhere in the criminal justice system. Each year, participating law enforcement agencies contribute reports either directly or through their state reporting programs. Summary data are provided in four types of files: (1) Offenses Known and Clearances by Arrest, (2) Property Stolen and Recovered, (3) Supplementary Homicide Reports (SHR), and (4) Police Employee (LEOKA) Data. The Supplementary Homicide Reports provide incident-based information on criminal homicides reported to the police. These homicides consist of murders, non-negligent manslaughter, and justifiable homicides. The data, provided monthly by UCR agencies, contain information describing the victim of each homicide, the offender, and the relationship between victim and offender.